2023
DOI: 10.1111/jan.15566
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of families and health professionals along the care continuum for low‐birth weight neonates: A constructivist grounded theory study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…The themes were broadly categorized into family-system and health system drivers. The four themes related to family-system drivers are described elsewhere [ 78 ]. In this paper, we focus on the six health systems drivers: strengthening 1) postnatal discharge; 2) review; 3) referral system; 4) efficient dissemination and implementation of guidelines; 5) supportive supervision and staff motivation and lastly; 6) investments into care coordination, training and human resource.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The themes were broadly categorized into family-system and health system drivers. The four themes related to family-system drivers are described elsewhere [ 78 ]. In this paper, we focus on the six health systems drivers: strengthening 1) postnatal discharge; 2) review; 3) referral system; 4) efficient dissemination and implementation of guidelines; 5) supportive supervision and staff motivation and lastly; 6) investments into care coordination, training and human resource.…”
Section: Resultsmentioning
confidence: 99%
“…Training health care professionals on family systems care can be an avenue to include families of LBW infants more into the care continuum for LBW infants. With a family systems care approach, the autonomy of mothers can be maintained through careful assessment of the family’s structure and gender’s influence, cultural beliefs and who should be with the mother based on her preferences [ 56 , 78 , 91 ]. This can enhance quality of care, reduce tension within the family as well as the financial burden for families and the health system [ 59 , 84 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, after implementing it for 6 meetings, the patient appeared cooperative, there was eye contact, the patient was willing to socialize and take part in activities with friends, the patient seemed no longer alone. And from the two patients it was found that complaints of hearing whispers were greatly reduced and they felt better every day after receiving guidance on controlling hallucinations from the nurse [9].…”
Section: Discussionmentioning
confidence: 99%
“…Planning the return of a baby with low birth weight from the hospital is a critical stage in the care of the baby. The mother's self-confidence level strongly influences home care success after hospital discharge (Schuler et al, 2023). The mother's confidence in caring for a low-birth-weight baby is crucial in ensuring that the baby gets the appropriate care for her medical needs.…”
Section: Introductionmentioning
confidence: 99%